S. A. STROIKOVA: MOTIVATIONAL TYPES OF GERMAN GASTRONOMIC NAMES (GASTRONIMS) - STROIKOVA, S. A (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. The sign system of food is one of the most important for human existence, which represents both the structure of consumption and maintenance of human life and its cultural preferences, the specifics of the sensory sphere of the people, taste as an aesthetic phenomenon. The names of German dishes were not the object of a comprehensive study; however, their onomasiological structures were interesting and specific material for revealing the cognitive mechanisms of ethnic consciousness and cultural priorities of the German people. This determines the relevance of cognitive-onomasiological analysis of the motivation of the system of these signs. Purpose. The purpose of the article is a comprehensive analysis of motivational types of German gastronomic names in the projection of their onomasiological structures on the cognitive basis of creation. Methods. The main research method is cognitive-onomasiological analysis, which involves two stages. The first stage is the interpretation of onomasiological structures of German names of dishes. According to the onomasiological structure, German gastronomic names are represented by composites and compound names. At the second stage of cognitive-onomasiological analysis the modeling of the structure of knowledge about the signified is carried out, which is based on the model of mental-psychonetic complex. Results. Depending on the status of the component of knowledge structure chosen by the motivator in the array of German gastronomic names, propositional-dictum, associative-metaphorical, precedent and mixed types of motivation are distinguished. The propositional-dictum type of motivation contains hyperonymic and predicate-argument varieties. In the array of researched German gastronomic names, the main propositional components chosen by the motivators of propositional structures are predicates of causative influence, terms of the object, locative, levels of quality and quantity. Another, associative-metaphorical type of motivation is metaphorical and is characterized by the choice of motivational signs from the spheres of other concepts. The closest to the associative-metaphorical motivation is precedent one, which is also characterized by the choice of a motivator from the associative-terminal sphere, which contains, along with figurative knowledge, a layer of cultural knowledge The mixed type of motivation combines propositional, associative-terminal and modular components of the mental-psychonetic complex. Originality. The scientific novelty of the research results is that the article characterizes the cognitive basis of the creation of German names of dishes, clarifies the types of motivational mechanisms of these names. The new is the definition of the main donor cultural codes that supply signs to the field of culinary. Conclusion. The naming of dishes in German is an interesting lexical group for analysis, which makes it possible to trace various connections in ethno consciousness. German gastronomic names represent different types of motivation (propositional-dictum, associative-metaphorical, precedent and mixed). We see the prospect of further research in a detailed analysis and establishment of the features of each type of motivation for gastronomic names in the German language.